Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/vaccines8030397
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Unstructured, Linear B-Cell Epitopes in SARS-CoV-2 Virion Proteins for Vaccine Development

Abstract: The efficacy of SARS-CoV-2 nucleic acid-based vaccines may be limited by proteolysis of the translated product due to anomalous protein folding. This may be the case for vaccines employing linear SARS-CoV-2 B-cell epitopes identified in previous studies since most of them participate in secondary structure formation. In contrast, we have employed a consensus of predictors for epitopic zones plus a structural filter for identifying 20 unstructured B-cell epitope-containing loops (uBCELs) in S, M, and N proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Epitopes are the basis of protein antigenicity, and they act a vital part in the preparation of specific antibodies against proteins, the computer-aided design of vaccines, especially in the recent tumor immunotherapy (Corral-Lugo et al 2020 ). Epitopes are divided into linear epitopes and conformational epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Epitopes are the basis of protein antigenicity, and they act a vital part in the preparation of specific antibodies against proteins, the computer-aided design of vaccines, especially in the recent tumor immunotherapy (Corral-Lugo et al 2020 ). Epitopes are divided into linear epitopes and conformational epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to S, N protein does not play direct role in viral attachment to epithelial cells of the upper and lower respiratory tracts so that anti-N antibodies are neither neutralizing nor protective against SARS-CoV in animal models [ 28 ]. In addition, this protein is ten-fold more abundant than S protein in the virion [ 29 ], very immunogenic [ 30 ], and extraordinarily enriched in flexible loops carrying validated and predicted B-cell epitopes [ 31 ]. Moreover, N protein is highly conserved among coronaviruses, probably due to high selective pressure to maintain numerous interactions with RNA in addition to viral and host proteins required by its role in virulence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sequences were aligned by Muscle 3.8 [ 35 ]. Linear B-cell epitopes were predicted in SARS-CoV-2 structural sequences as described elsewhere [ 31 ]. Transmembrane helices were predicted with Phobius [ 36 ] and not considered to define B-cell epitopes since they are buried, i.e., not accessible, in the membrane.…”
Section: Methodsmentioning
confidence: 99%
“…baumannii therefore epitomizes microorganisms that require alternatives to small molecule-based antimicrobial therapy (10). Multiple studies have reported protective immunity against A. baumannii after prophylactic vaccination or administration of antibodies in rodent infection models (reviewed in (11)). These preclinical results suggest that prophylatic vaccination and passive therapeutics could contribute to the prevention and treatment of infections caused by this pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…A monoclonal antibody against the A. baumannii capsular polysaccharide was able to rescue infected mice in a lethal sepsis model (12). Candidates that have been tested in preclinical vaccine models include the OmpA porin (13), Ata (14) and Bap (15), and more recently BamA (16) and Omp22 (17) among others (11). However, many of these candidates provide only partial protection against infection, as exemplified by vaccination with the OmpA porin (13).…”
Section: Introductionmentioning
confidence: 99%